1998
DOI: 10.1093/humrep/13.11.3247
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy following intracytoplasmic sperm injection from an HIV-1- seropositive man

Abstract: The first pregnancy achieved in a seronegative woman following in-vitro fecundation through intracytoplasmic sperm (ICSI) injection from a man with autoimmune deficiency syndrome (AIDS; HIV-1 carrier) is reported. The semen was prepared by PureSperm and swim-up techniques. Some of the motile spermatozoa obtained were used to detect the presence of HIV-1 using the polymerase chain reaction technique. HIV-1 in DNA or RNA form was not detected using this technique. The remaining spermatozoa were frozen. Ovarian s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(25 citation statements)
references
References 0 publications
1
23
0
1
Order By: Relevance
“…The first pregnancy achieved in a seronegative woman following in vitro fecundation through intracytoplasmic sperm (ICSI) injection from a man with autoimmune deficiency syndrome (AIDS; HIV-1 carrier) was reported in 1998 [7]. The semen was prepared by PureSperm and swim-up techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The first pregnancy achieved in a seronegative woman following in vitro fecundation through intracytoplasmic sperm (ICSI) injection from a man with autoimmune deficiency syndrome (AIDS; HIV-1 carrier) was reported in 1998 [7]. The semen was prepared by PureSperm and swim-up techniques.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, both recent and earlier studies concluded that purification of motile spermatozoa by either the discontinuous gradient or swim-up method, or even by a combination of these techniques, reduces the number of HIV and/or HCV particles in semen to undetectable levels 8,14,17,18,24,28,32 , making it possible for serodiscordant couples to conceive a child by means of assisted reproduction techniques with minimum risk of seroconversion 14,15,32 .…”
Section: Introductionmentioning
confidence: 92%
“…As these couples cannot stop using condoms, lest they infect their seronegative partner or the newborn, it is essential to treat the infected semen with effective laboratory techniques that not only isolate the best spermatozoa, but also remove HIV and HCV infected cells from the semen. This is achieved in many studies by using the semen washing technique together with the swim up 26 method to purify the infected semen 17,18,24,32 .…”
Section: Introductionmentioning
confidence: 99%
“…There was a trend toward shorter cycles and more cycle variability among seropositive women with high viral loads and low CD4 cell counts. A study comparing women with CD4 cell counts between 200 and 500 cells/µl to women with CD4 cell counts under 100 cells/µl demonstrated a prevalence of amenorrhea of 9% and 19% respectively, illustrating an association between immunosuppression and amenorrhea, at least at the more severe end of the spectrum (21).…”
Section: Menstrual Disordersmentioning
confidence: 99%
“…The serodiscordant couple contemplating timed intercourse should be counseled against this, as transmission occurs in 1 of 500 to 1 of 1000 instances of unsafe sex, with a 4.3% horizontal transmission rate reported in couples using timed intercourse to conceive (200). If they do proceed with timed intercourse, they should be counseled not to start until the male's viral load is undetectable, to avoid sexual contact if either partner has any other untreated sexual infections, ulcers, or bleeding, and to use ovulation predictors to accurately time their sexual contacts.…”
Section: Fertilitymentioning
confidence: 99%